Tracing the Footsteps of Local Wisdom: An Analysis of Tha'buthaan Culture in Arjasa District, Jember Regency, Viewed from the Seven Cultural Elements - Nur Safitri; Novita Ambarsari; Roihatus Fafaisa; Ilfiana Firzaq Arifin (Warisan: Journal of History and Cultural Heritage, 2024)
Tha'buthaaan art in Arjasa District, Jember, East Java, is one of the oldest arts that still exists today. This art has high cultural and historical value and reflects the identity of the local community. This research aims to understand the existence of tha'buthaan art in Arjasa District from an anthropological perspective. The method used is qualitative with an anthropological approach, collecting information through interviews, observations, and literature studies. The results of the research prove that this tha'buthaan has social, cultural, and religious functions. The existence of tha'buthaan art is faced with various challenges, which also require efforts from various parties, not just artists. These efforts must be made to maintain this art. By understanding the extent of this art from an anthropological perspective, it is hoped that it can help in conservation efforts and promote the significance of traditional arts in the modern era.